1996
DOI: 10.1074/jbc.271.8.3988
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging of Nitrogen Dioxide, Thiyl, and Sulfonyl Free Radicals by the Nutritional Antioxidant ²-Carotene

Abstract: ؉ and radical-addition, [RSO 2 ⅐⅐⅐␤-carotene] ⅐ in an approximate 3:1 ratio. The ␤-carotene radical-cation and adduct-radicals are highly resonance stabilized and undergo slow bimolecular decay to non-radical products. These carotenoidderived radicals react differently with oxygen, a factor which is expected to influence the antioxidant activity of ␤-carotene within tissues of varying oxygen tension in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 62 publications
9
144
1
1
Order By: Relevance
“…Interaction of ß- carotene with NO2 released little HNO2 or NO under the present conditions and nitrogen atoms from NO2 might be tightly bound to the ß-carotene molecule. The present results are somewhat different from those with respect to the release of nitrogen species [8,9]. It has been shown that N 0 2 is converted by ß-carotene into nitrosating agents in the dark and into NO in the light [8], and that N 0 2 generated by pulse radiolysis is converted into H N 0 2 by ß-carotene [9].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Interaction of ß- carotene with NO2 released little HNO2 or NO under the present conditions and nitrogen atoms from NO2 might be tightly bound to the ß-carotene molecule. The present results are somewhat different from those with respect to the release of nitrogen species [8,9]. It has been shown that N 0 2 is converted by ß-carotene into nitrosating agents in the dark and into NO in the light [8], and that N 0 2 generated by pulse radiolysis is converted into H N 0 2 by ß-carotene [9].…”
Section: Discussioncontrasting
confidence: 54%
“…A recent study by Cooney et al [8] has shown that NO2 is converted by ß-carotene into nitrosating agents in the dark and into NO in the light. Everett et al [9] have shown that reaction of ß-carotene with N0 2 generated by pulse radiolysis gives ß-carotene radical cation and HN0 2 . In the present study, the reactivity of ß-carotene toward NO, NO z , ONOOH/ONOO and 3-morpholinosydononimine (SIN-1) that generates ONOOH/ONOO" was examined.…”
Section: Introductionmentioning
confidence: 99%
“…The faster oxidation can be attributed to the oxidation of crocin by NO 2 and N 2 O 3 formed by reactions 3 and 4, respectively, in addition to the reaction of O 2 with crocin radicals. If crocin is reacted with NO 2 and/or N 2 O 3 , it can function as a scavenger of reactive nitrogen oxide species such as β-carotene and other carotenoids (Cooney et al, 1994;Everett et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of 13-carotene with peroxyl radicals generated during lipid peroxidation has been suggested to lead to formation of a radical adduct [[3-car...RO2]" [16]. Mechanisms of free radical scavenging have been investigated [17] by pulse radiolytic generation of nitrogen dioxide radicals (NO~), thiyl radicals (RS') and sulphonyl radicals (RSO~), which are rapidly scavenged by I~-carotene. The mechanism for the scavenging of the NO~ radical has been described as that of electron donation with radical cation formation [ [3-carotene] "+ whereas the scavenging of thiyl radicals involves the generation of a radical adduct [13-car..RS]'.…”
Section: Introductionmentioning
confidence: 99%